Characterization of Staphylococcus aureus isolated from small ruminants and farm workers in Albatinah south, the Sultanate of Oman - Almakhladi, Salim Sulaiman Rashid (2018)
Staphylococcus aureus has long been recognised as an important pathogen causing nosocomial, community and livestock-associated infections worldwide. The prevalence and incidence rates of S. aureus and methicillin resistant S. aureus (MRSA) infections are on the rise worldwide but differ in the rates from country to another. Similarly, in the Sultanate of Oman there is a significant increase in the incidence of MRSA infection at major hospitals. While there are few numbers of research on the organism in human, there is no information on S. aureus and MRSA carriage among livestock and livestock workers in the country to date. This study is designed to investigate the prevalence of nasal carriage of S. aureus and MRSA in goat, sheep, and farm workers and subsequently the isolates were characterized using phenotypic and genotypic methods. Antibiotic susceptibility test (AST) was carried out using the minimum inhibitory concentration (MIC). Molecular identification was performed for the presence of the nuc gene and mecA gene, while molecular typing was done for six S. aureus isolates using multilocus sequencing typing (MSLT). The sampling frame for sample collection from all the different Wilayats (Districts) of Al Batinah South Governorate in the Sultanate of Oman was calculated and designed according to the Agricultural Census, Ministry of Agriculture and Fisheries, Sultanate of Oman. A total of 876 nasal swab samples were collected from Barka (n=341), Rustaq (n=209), Musanah (n=190), Nakhal (n=60), Wadi Al Maawil (n=49), Al and Alawaby (n=27). The samples were from goat (n=413), sheep (n=408) and farm workers (n=55). Upon identification and confirmation of the bacteria using PCR detection of nuc and mecA gene, 18 samples (2.05%) were positive for S. aureus which included five isolates (1.21%) from goats, 6 from sheep (1.47%) and 7 from farm workers (12.73%). In total, 18/876 (2.06%) of the livestock and farm workers were positive for S. aureus. In goats, 5/413 (1.21%) of the samples were positive for S. aureus. In sheep, 6/408 (1.47%) of the samples were positive for S. aureus. In farm workers, 7/55 (12.73%) of the samples were positive for S. aureus, and 1/7 (14.29%) of them had MRSA. Only one isolate was positive for mecA gene confirming the presence of only one MRSA in the tested samples. Minimum Inhibitory Concentration results showed that the isolates were mostly susceptible to the majority of the tested antibiotics which comprised of; benzylpenicillin, oxacillin, gentamicin, tobramycin, levofloxacin, moxifloxacin, erythromycin, clindamycin, linezolid, teicoplanin, vancomycin, tetracycline, tigecycline, fosfomycin, nitrofurantoin, fusidic acid, mupirocin, rifampicin, trimethoprim/sulfamethoxazole. It was found that 10/18 (55.56%) were resistant to benzylpenicillin, 7/18 (38.89%) were resistant to erythromycin, 5/18 (27.78%) were resistant to clindamycin, 1/18 (5.65%) were resistant to oxacillin and tetracycline and 3/18 (16.67%) were intermediately resistant to levofloxacin. Multilocus sequencing typing (MLST) performed on six isolates revealed from different sequence types (STs); ST1290, ST522, ST2884 and ST6. This study reported that the prevalence of nasal carriage of S. aureus in goat, sheep and farm workers is low in Albatinah South. The prevalence of MRSA was also very low. Neither sheep nor goat had MRSA. This study provides the fundamental information on the current status of S. aureus and MRSA in the small ruminants and humans having close contact with the animals. It also indicates the need for preventive measures to maintains the low prevalence of S. aureus and MRSA in small ruminant and to control the spread of S. aureus in the livestock, in Oman.